Naga Liman Pencana Kencana Train Caruban Nagari's Multicultural Symbols: Inculturalization 0f Nusantara Art in Cultural Arts Education - Suardana, Wayan; Fikriyyati, Indah; Maulana A, Deden (International Journal of Psychosocial Rehabilitation, 2020)
Cirebon is referred to as a multicultural area, so the term Cirebon comes from Caruban, which means mixture. Since the mid-15th century, there have been a number of censuses of statistical data from each culture, such as Javanese, Sundanese, Chinese, Persians, Majapahit, and others. Therefore, Paksi Naga Liman is a form or symbol of the multicultural life of the nation and state itself. Naga Liman Kencana Train is Sultan Kanoman's great train; in Naga Liman Paksi Train there is the teaching 'Hablu Minal Alam', the union of three animal elements that live in three different realms, namely air, sea, and land. But so far, Cirebon itself has not fully implemented or incorporated the existing Art forms in the Naga Liman Paksi Train in the world of Education, especially in schools, so that not a few elementary, junior high or even high school students understand and understand that it is on the Pencana Kencana Train Naga Liman has multicultural values that represent Cirebon as being born from a variety of cultures, races, religions and ethnicities. This research uses a qualitative method, which is written descriptively. Methods of data collection were carried out through field studies in the form of: interviews, observations, visiting the Kanoman palace museum, examining each symbol in the chariot train, and library study.